2019
DOI: 10.3390/foods9010032
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Freeze-Drying Conditions on the Physico-Chemical Properties and Bioactive Compounds of a Freeze-Dried Orange Puree

Abstract: Fruits are essential for a healthy diet, as they contribute to the prevention of cardiovascular diseases and some cancers, which is attributed to their high bioactive compound content contributing to their antioxidant capacity. Nevertheless, fruits have a short shelf life due to their high-water content, and freeze-drying is a well-known technique to preserve their nutritive quality. However, it is an expensive technology, both due to the use of low pressure and long processing time. Therefore, an optimisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 38 publications
(51 reference statements)
4
58
0
1
Order By: Relevance
“…Similar phenomena were observed for freeze-dried apples when the heating shelf temperature exceeded 55 °C [ 85 ]. Silva-Espinoza et al [ 14 ], during the freeze-drying of orange puree, did not observe changes in lightness L* with an increasing process temperature from 30 to 50 °C, but the chroma C* was enhanced at the higher shelf temperatures of 40 and 50 °C and the hue angle decreased for temperatures below 50 °C.…”
Section: Effect Of Freeze-drying Conditions Of the Selected Physicmentioning
confidence: 98%
See 3 more Smart Citations
“…Similar phenomena were observed for freeze-dried apples when the heating shelf temperature exceeded 55 °C [ 85 ]. Silva-Espinoza et al [ 14 ], during the freeze-drying of orange puree, did not observe changes in lightness L* with an increasing process temperature from 30 to 50 °C, but the chroma C* was enhanced at the higher shelf temperatures of 40 and 50 °C and the hue angle decreased for temperatures below 50 °C.…”
Section: Effect Of Freeze-drying Conditions Of the Selected Physicmentioning
confidence: 98%
“…The effect of shelf temperature on the texture of freeze-dried products can be found in a few research studies. Silva-Espinoza et al [ 14 ] noted that the compressed cylinders of freeze-dried orange puree obtained at a higher shelf temperature behaved the same as a material with higher rigidity. Additionally, the values of the slope of the fracture curve were related to the sample resistance and the deformation increase with raising shelf temperature.…”
Section: Effect Of Freeze-drying Conditions Of the Selected Physicmentioning
confidence: 99%
See 2 more Smart Citations
“…The freezing rate is, however, a critical parameter contributing to the distribution and morphological variation observed in the microstructure of freeze-dried food materials. Silva-Espinoza et al [99] reported the influence of the freeze-drying rate on orange puree with added gum arabic and bamboo fiber. In the research, it was established that a slow rate of freezing resulted in the formation of bigger ice crystals and an expansion of the cells in the structure, resulting in larger pore formation.…”
Section: Impact Of Freezing Rate On Crystallization and Microstructurementioning
confidence: 99%